Analysis of Nazhir Accountability Implementation in Empowerment of Productive Waqf in Indonesia - Henik Hari Astuti; Hendri Tanjung (Tazkia Islamic Finance and Business Review, 2019)
This study aims to find constraints or problems in applying accountability, find solutions and strategies that can be done by nazhir and related institutions, namely Ministry of Religion and BWI using the ANP (Analytical Network Process) method. This research was conducted in the period 2015 to 2018. The results of this study indicate that many problems in the implementation of accountability include people's understanding of waqf is still low, nazhir is not professional, the system is inadequate, nazhir is not transparent and BWI and Ministry of Religion are not optimal. The implications of this research are in the form of a theory of problem mapping formulation, accountability strategies and solutions that can be applied by nazhir, BWI and Ministry of Religion as productive waqf management organisations to increase their productivity to improve the welfare of the people.